Neurofilament Light Chain Levels in Anti-NMDAR Encephalitis and Primary Psychiatric Psychosis. (5th April 2022) - Guasp, Mar; Martín-Aguilar, Lorena; Sabater, Lidia; Bioque, Miquel; Armangué, Thaís; Martínez-Hernández, Eugenia; Landa, Jon; Maudes, Estibaliz; Borràs, Roger; Muñoz-Lopetegi, Amaia; Saiz, Albert; Castro-Fornieles, Josefina; et al.
Abstract : Background and Objectives: An important challenge in diagnosing anti–NMDA receptor (NMDAR) encephalitis (NMDARe) is differentiating it from a first episode of psychosis (FEP) caused by a psychiatric disease (pFEP). CSF antibody testing distinguishes these diseases, but spinal taps are difficult to obtain in psychiatric facilities. A separate problem is the lack of biomarkers of NMDARe severity and outcome. Here we assessed the performance of neurofilament light chain (NfL) testing in these settings. Methods: In this observational study, NfL levels were determined with single-molecule array in patients with NMDARe, pFEP, herpes simplex encephalitis (HSE), and healthy participants (HC), with the last 2 groups used as controls. Receiver operating characteristic (ROC) analyses were performed to assess the prediction accuracy of serum NfL (sNfL) levels for NMDARe and pFEP and to obtain clinically useful cutoffs. Results: One hundred eighteen patients with NMDARe (33 with isolated psychosis at presentation), 45 with pFEP, 36 with HSE, and 36 HC were studied. Patients with NMDARe with seizures/status epilepticus, intensive care unit admission, and CSF pleocytosis (>20 white blood cells/µL) and without early immunotherapy were more likely to have higher NfL (mainly in CSF) than individuals with NMDARe without these features. NfL levels at diagnosis of NMDARe did not correlate with outcome at 1-year follow-up assessed with the modified Rankin Scale. Patients with NMDARe had significantly higher sNfL than individuals with pFEP and HC and lower sNfL than patients with HSE. ROC analysis of sNfL between NMDARe with isolated psychosis and pFEP provided an area under the curve of 0.93 (95% CI 0.87–0.99) and an sNfL cutoff ≥15 pg/mL to distinguish these disorders (sensitivity 85%, specificity 96%, positive likelihood ratio 19.3). Forty-three of 45 (96%) patients with pFEP had sNfL<15 pg/mL, whereas only 5 of 33 (15%) with NMDARe with isolated psychosis were below this cutoff (risk estimation NMDARe vs pFEP: odds ratio 120.4 [95% CI 21.8–664], p < 0.001). None of the patients with HSE and 35 of 36 (97%) HC had sNfL<15 pg/mL. Discussion: NfL measured at diagnosis of NMDARe associated with features of disease severity but not with long-term outcome. Young patients with FEP and sNfL ≥15 pg/mL had a 120 times higher chance of having NMDARe than those with pFEP. This cutoff correctly classified 96% of patients with pFEP and 85% of patients with NMDARe with isolated psychosis. Patients with FEP of unclear etiology and sNfL ≥15 pg/mL should undergo CSF NMDAR antibody testing.